Hollywood special effects with Adobe Premiere Elements 3 - Plumer, Carl (Peachpit Press, 2006)
Hollywood Special Effects with Adobe Premiere Elements 3 is a book that will help users get to the next level in video editing, and that next level goes beyond simply splicing together clips and creating simple titles. In no time readers will be overlaying multiple tracks of videos and adjusting transparency; creating Picture-in-Picture overlays; using key frames and motion paths; setting and refining greenscreens and bluescreens; using color effects for emotional impact; and a whole range of other special effects to help them tell their story. What sets this book apart is the author's expertise in carefully showing readers how to execute each of these effects step-by-step in a clear and friendly writing style. With this book, budding filmmakers will be well on their way to becoming the next George Lucas! The accompanying DVD contains royalty free music, sound effects, and video clips from Artbeats, Digital Juice, TwistedTracks, and the Footage Firm (among others).